Macroeconomic determinants on spain tax revenue / Amirul Izet Syamim Anuar - Anuar, Amirul Izet Syamim (2018)
Taxation is one method of transferring resources from the private to the public sectors. Taxation is the usually the most important and main source of the government. However, the tax system has been one of the victims of numerous economic crises. Tax collections are still very low leading to large fiscal deficits. The fiscal deficit is the core issue of most of the developing countries over the past several decades. The reason behind the large increase in fiscal imbalance is the rapid expansion in expenditure and low revenue income. The issue that can be seen on this study is whether the macroeconomic factors is relevant with tax revenue. This study is to examine whether the macroeconomic variables determine on Spain tax revenue. The purpose of the study is to examine the determinants of tax revenue in Spain. The dependent variable for this study is tax revenue. The independent variable for this study is the gross domestic product (GDP), trade openness and inflation rate. The data for this study are analysed based on a time series data analysis. This study uses the collection of data from secondary data. The data is obtained from World Development Indicators. The data consists of Spain. Next, the data period 1986 to 2016 was chosen for this study. This study used the descriptive analysis and followed by stationary test. After that, this study used correlation analysis. The positive significant relationship between dependent variable and independent variable are expected in this study. This study also included regression analysis and normality test.